Dynamic changes in peripheral inflammation as a risk factor for perioperative sleep disturbances in elderly patients undergoing laparoscopic hepatobiliary surgery - Wei, Lai; Zhu, Xiaoyu; Zhao, Yiming; Zou, Yi; Hu, Tao; Huang, Qian; Li, Jieqiong; Pan, Bingbing; Kong, Gaoyin; Tan, Siyou; Chen, Wenyan (Frontiers in Neurology, 2025)
BackgroundElderly surgical patients are at high risk of perioperative sleep disturbances (PSD), and the underlying pathogenic mechanisms remain unclear. The relationship between peripheral inflammatory status and PSD pathogenesis currently lacks substantial clinical evidence.ObjectiveThis study aims to evaluate the association between peripheral inflammation indicators and PSD in elderly patients undergoing laparoscopic hepatobiliary surgery, and to analyze the dynamic changes in peripheral inflammation in PSD patients throughout the perioperative period.Method and materialsUsing retrospective data, this study compares peripheral inflammatory markers (NLR, MLR, PLR, SII, IL-6, and IL-10) in patients with PSD vs. those with normal sleep patterns before and after surgery. Receiver operating characteristic (ROC) curves were employed to evaluate the discriminative power of these indicators for PSD. Logistic regression models were employed to assess risk associations between inflammatory markers and PSD. Dynamic changes in peripheral inflammation were compared before surgery, on the day the surgery ended, and 1 day post-surgery between patients with PSD and those with normal sleep, exploring potential correlations with PSD pathogenesis.ResultThe study ultimately included clinical data from 156 patients. Findings indicated that elevated NLR and SII levels before and after surgery, alongside decreased plasma IL-10 levels post-surgery, are associated with a higher incidence of PSD. Peripheral inflammatory markers on the day of surgery were not significantly predictive of post-PSD. Multivariable logistic regression analyses identified NLR, SII, IL-6, and IL-10 as independent predictors of pre-PSD, while NLR, SII, and IL-10 remained independently associated with post-PSD.ConclusionDynamic changes in peripheral inflammation during the perioperative period are associated with PSD in elderly patients undergoing laparoscopic hepatobiliary surgery. These findings may support the early identification and screening of high-risk PSD patients, providing new insights into the underlying mechanisms of PSD pathogenesis.